The Effect of Nicotinamide Riboside, an NAD + Precursor, on Glycolysis and NAD + Salvage Pathway in Alcohol-Stimulated Macrophages. (14th June 2022) - Kang, Hyunju; Kim, Mi-Bo; Park, Young-Ki; Lee, Ji-young
Abstract: Objectives: We demonstrated that ethanol decreased cellular NAD + levels not only by consuming it but by repressing the expression of genes involved in the NAD + salvage pathway, consequently altering cellular bioenergetics in macrophages. Therefore, we explored whether nicotinamide riboside (NR), an NAD + precursor, could restore cellular NAD + and reverse changes in glycolytic capacities triggered by ethanol alone or ethanol with FK866, an inhibitor of nicotinamide phosphoribosyltransferase (NAMPT), the rate-limiting enzyme of the NAD + salvage pathway. Methods: RAW 264.7 macrophages were treated with 80 mM ethanol with or without 1 mM of NR and 50 nM FK866 for 72 h. Expression of genes involved in the NAD + salvage pathway and glycolysis and cellular NAD + levels were measured. Parameters related to glycolysis were determined using a Seahorse XFe24 Extracellular Flux analyzer. Sirtuin 1 (SIRT1) was inhibited by its inhibitor sirtinol or siRNA-mediated knockdown or activated by resveratrol to evaluate its contribution to the effects of ethanol on the NAD + salvage pathway. Results: NR significantly increased, but NAMPT inhibition decreased cellular NAD + content in control and ethanol-treated cells. However, ethanol decreased, and NAMPT inhibition further lowered NAD + content. Decreases in cellular NAD + and mRNA levels of genes in the NAD + salvage pathway, such as Nmrk1, Nampt, Nmnat1, and Nmnat3, by ethanol and FK866 were attenuated by NR. Interestingly, both NR and FK866 diminished increases in glycolytic capacity, glycolytic reserve, and non-glycolytic acidification caused by ethanol. Ethanol increased the expression and activity of hypoxia-inducible factor 1α (HIF1α) and glycolytic genes, and pyruvate dehydrogenase (PDH) phosphorylation, all of which were attenuated by NR and FK866, with the latter being more potent. Ethanol and FK866, to a much greater extent, repressed Sirt1 expression. SIRT1 inhibition reduced Nampt expression, but SIRT1 activation and NR led to the opposite effects in ethanol-exposed macrophages. Conclusions: NR attenuates decreases in cellular NAD + content and glycolytic capacities by ethanol alone or ethanol with NAMPT inhibition at least partly through the activation of the SIRT1 pathway in macrophages. Funding Sources: University of Connecticut College of Agriculture, Health and Natural Resources & USDA multistate Hatch W4002.